Pendidikan Inklusi Solusi Utama Untuk Anak Penyandang Disabilitas - Munauwarah, Rahmadin; Zahra, Ashadatul; Supandi, Muhamad; Restiany, Risma Ardianti; Afrizal, Dimas (YASIN, 2021)
Children with disabilities have the same rights as children in general to get an education. Unfortunately, the availability of adequate education for children with special needs is not adequate and equal. Because the provision of special schools only in big cities. The research method used is qualitative research with a literature study approach. The results showed that inclusive education came as the main solution to overcome children with disabilities. The purpose of establishing inclusive schools is to minimize the impact caused by an exclusive attitude. Inclusive schools also provide opportunities for children with special needs and less able to pursue postgraduate education.